The Influence of Competence and Utilization of Information Technology on the Quality of Financial Reports with Education as a Moderator: Case Study at the Finance Office of Kodam XIV/Hasanuddin as UAPPA-W - Alimin, Muh; Tangngisalu, Jannati; Lalo, Annas (Golden Ratio of Auditing Research, 2026)
The purpose of this study is to analyze the influence of competency and utilization of information technology on the quality of financial reports, with education as a moderator (a case study at the Finance Office of the XIV/Hasanuddin Regional Military Command (UAPPA-W). The population of this study is the finance department, which has duties and responsibilities in financial management that directly and indirectly influence the quality of financial reports at the XIV/Hasanuddin Regional Military Command (UAPPA-W). Data collection was carried out by distributing 150 questionnaires to the Finance Unit of the XIV/Hasanuddin Regional Military Command (UAPPA-W). However, the minimum sample size required is 15 to 20 times the number of variables used (4 variables), resulting in a total sample size of 80. The sampling technique used an accidental method. Researchers at the Finance Office of the XIV/Hasanuddin Regional Military Command (KODAM XIV/HASANUDDIN) voluntarily completed a research questionnaire over a one-month period. Data analysis was performed using PLS SEM with the assistance of the SmartPLS 4 program. The results of this study indicate that the variables of competence and utilization of information technology have a significant positive effect on the quality of financial reports. The variable of Competence on Financial Report Quality, with Education as a Moderator, has a significant positive effect on the quality of financial reports. However, the variable of utilization of information technology has a significant negative effect on the quality of financial reports at the Finance Office of the XIV/Hasanuddin Regional Military Command (UAPPA-W).